ART Versus Reinsurance: The Disciplining Effect of Information Insensitivity - Silke Brandts; Christian Laux (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We provide a novel benefit of Alternative Risk Transfer (ART) products with parametric or index triggers. When a reinsurer has private information about his client's risk, outside reinsurers will price their reinsurance offer less aggressively. Outsiders are subject to adverse selection as only a high-risk insurer might find it optimal to change reinsurers. This creates a hold-up problem that allows the incumbent to extract an information rent. An information-insensitive ART product with a parametric or index trigger is not subject to adverse selection. It can therefore be used to compete against an informed reinsurer, thereby reducing the premium that a low-risk insurer has to pay for the indemnity contract. However, ART products exhibit an interesting fate in our model as they are useful, but not used in equilibrium because of basis-risk.
urn:nbn:de:hebis:30-18119
Keywords: D82; G22; 330; Cat Bonds; Risk Transfer; Index Trigger; Adverse Selection